2017
DOI: 10.1016/j.cognition.2017.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Waiting for lexical access: Cochlear implants or severely degraded input lead listeners to process speech less incrementally

Abstract: Spoken language unfolds over time. Consequently, there are brief periods of ambiguity, when incomplete input can match many possible words. Typical listeners solve this problem by immediately activating multiple candidates which compete for recognition. In two experiments using the visual world paradigm, we examined real-time lexical competition in prelingually deaf cochlear implant (CI) users, and normal hearing (NH) adults listening to severely degraded speech. In Experiment 1, adolescent CI users and NH con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

15
137
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 87 publications
(170 citation statements)
references
References 83 publications
(163 reference statements)
15
137
0
Order By: Relevance
“…Rather, the robust evidence for immediate integration for other speech cues (McMurray, Clayards, et al, 2008;Reinisch & Sjerps, 2013;Toscano & McMurray, 2012) and factors (Kingston et al, 2016;Mitterer & Reinisch, 2013;Toscano & McMurray, 2015) raises the possibility of a hybrid model combing both implicit memory processes deriving from activation or recurrence, and explicit memory of some kind. It is also consistent with more recent work (McMurray, Farris-Trimble, & Rigler, 2017) showing that pre-lingually deaf cohlear implant users may also delay lexical access to accumulate information, potentially as a way to minimize competition.…”
Section: General Implications For Language Processingsupporting
confidence: 90%
“…Rather, the robust evidence for immediate integration for other speech cues (McMurray, Clayards, et al, 2008;Reinisch & Sjerps, 2013;Toscano & McMurray, 2012) and factors (Kingston et al, 2016;Mitterer & Reinisch, 2013;Toscano & McMurray, 2015) raises the possibility of a hybrid model combing both implicit memory processes deriving from activation or recurrence, and explicit memory of some kind. It is also consistent with more recent work (McMurray, Farris-Trimble, & Rigler, 2017) showing that pre-lingually deaf cohlear implant users may also delay lexical access to accumulate information, potentially as a way to minimize competition.…”
Section: General Implications For Language Processingsupporting
confidence: 90%
“…factors raises the possibility of a hybrid model combing both implicit memory processes deriving from activation or recurrence, and explicit memory of some kind. It is also consistent with more recent work (McMurray, Farris-Trimble, & Rigler, 2017) showing that pre-lingually deaf cohlear implant users may also delay lexical access to accumulate information, potentially as a way to minimize competition.…”
Section: General Implications For Language Processingsupporting
confidence: 90%
“…Its popularity can be 19 attributed to its sensitivity to a wide range of cognitive tasks and processing that relate 20 to the concept of listening effort [3,14,15]. Past studies have shown that pupil size 21 varies with different speech intelligibility, hearing impairment, lexical manipulation, 22 masker type, spectral resolution, memory load and divided/focused attention [4,[16][17][18][19][20][21][22][23]. 23Typically, when task demands increase, for instance, with lower SNR, degraded spectral 24 resolution or more digits to remember, pupil size increases.…”
mentioning
confidence: 99%